The gender of reparations : unsettling sexual hierarchies while redressing human rights violations - Rubio-Marín, Ruth (Cambridge University Press, 2009)
"Reparations programs seeking to provide for victims of gross and systematic human rights violations are becoming an increasingly frequent feature of transitional and post-conflict processes. Given that women represent a very large proportion of the victims of these conflicts and the authoritarianism generating them, and that women arguably experience conflicts in a distinct manner, it makes sense to examine whether reparations programs can be designed to redress women more fairly and efficiently and seek to subvert gender hierarchies that often antecede the conflict." "Focusing on themes such as reparations for victims of sexual and reproductive violence, reparations for children and other family members, as well as gendered understandings of monetary, symbolic, and collective reparations, The Gender of Reparations gathers information about how past or existing reparations projects dealt with gender issues, identifies best practices to the extent possible, and articulates innovative approaches and guidelines to the integration of a gender perspective in the design and implementation of reparations for victims of human rights violations."--Jacket